Strategi Pengelolaan Sumber Daya Manusia pada Generasi Z Tantangan dan Peluang di Era Digital Untuk Meningkatkan Kematangan Karir - Aprilita, Aprilita (Sahabat Publikasi, 2024)
The importance of adapting human resource management (HRM) strategies becomes increasingly fundamental in the rapid development of technology and changing workforce needs in this digital era. The objective of this research is to explore how HRM strategies can be adapted to meet the challenges and opportunities faced by Generation Z in the digital era, with a focus on enhancing career maturity. Additionally, the aim is to identify key factors in the effective implementation of HRM strategies for Generation Z that contribute positively to career maturity in the digital era. In the research titled